(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
The article examines the role of color detail in the organization of artistic space in A.P. Chekhov’s Three Sisters. The analysis demonstrates that in Chekhov’s dramaturgy color performs not a decorative but a structuring function: it participates in the construction of the stage world, reveals the correlation between memory and the present, emphasizes the changing internal status of the Prozorov house, and helps disclose the process by which the heroines become alienated from a space that had once embodied family unity and cultural measure.